TERPENES OF Melipona quadrifasciata GEOPROPOLIS - Marta S. D. Freitas; Matheus H. O. de Sousa; Alexandre Piccinini; Luiz Antonio Mendonça Alves da Costa; Neusa F. de Moura (Química Nova)
Melipona quadrifasciata is a stingless bee native to Brazil, known for producing a geopropolis with complex composition and diverse biological activity. The study aimed to identify the terpenes present in geopropolis collected from Melipona quadrifasciata colonies located in the state of Rio Grande do Sul, Brazil, to establish a geographic profile that enhances the understanding of the phytochemical composition of geopropolis from southern Brazil. The volatile fraction was analyzed by headspace-gas chromatography/mass spectrometry (HS-GC/MS) and identified fifty-six (56) mono- and sesquiterpenes, with particularly high concentrations of α- and β-pinene. These two compounds were present in all geopropolis samples at concentrations exceeding 50% and were identified as geographical markers of M. quadrifasciata geopropolis from the state of Rio Grande do Sul. Additionally, gas chromatography-mass spectrometry (GC-MS) analysis of the hexane fraction obtained via cold extraction under ultrasound revealed the presence of abietane diterpenes and pentacyclic triterpenes, particularly amyrins, with α-amyrin presented in all geopropolis samples.